Activation of inflammatory responses in human U937 macrophages by particulate matter collected from dairy farms: an in vitro expression analysis of pro-inflammatory markers - A Vogel Christoph F; Garcia Johnny; Wu Dalei; Mitchell Diane C; Zhang Yanhong; Kado Norman Y; Wong Patrick; Trujillo Danitza; Lollies Anna; Bennet Deborah; Schenker Marc B; Mitloehner Frank M (BMC, 2012)
Abstract Background The purpose of the present study was to investigate activation of inflammatory markers in human macrophages derived from the U937 cell line after exposure to particulate matter (PM) collected on dairy farms in California and to identify the most potent components of the PM. Methods PM from different dairies were collected and tested to induce an inflammatory response determined by the expression of various pro-inflammatory genes, such as Interleukin (IL)-8, in U937 derived macrophages. Gel shift and luciferase reporter assays were performed to examine the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and Toll-like-receptor 4 (TLR4). Results Macrophage exposure to PM derived from dairy farms significantly activated expression of pro-inflammatory genes, including IL-8, cyclooxygenase 2 and Tumor necrosis factor-alpha, which are hallmarks of inflammation. Acute phase proteins, such as serum amyloid A and IL-6, were also significantly upregulated in macrophages treated with PM from dairies. Coarse PM fractions demonstrated more pro-inflammatory activity on an equal-dose basis than fine PM. Urban PM collected from the same region as the dairy farms was associated with a lower concentration of endotoxin and produced significantly less IL-8 expression compared to PM collected on the dairy farms. Conclusion The present study provides evidence that the endotoxin components of the particles collected on dairies play a major role in mediating an inflammatory response through activation of TLR4 and NF-κB signaling.